Market trends and consumer demand for fresh berries - Sobekova, Kristina; Thomsen, Michael R.; Ahrendsen, Bruce L. (Applied Studies in Agribusiness and Commerce, 2013)
We present an analysis of markets for fresh strawberries, blueberries, blackberries and raspberries in the United States during 2008–2011. We use weekly panel data covering supermarket purchases in 52 cities. The primary goal is to estimate demand elasticities for fresh berries and thereby provide a better understanding of consumer behaviour in response to price changes and the nature of competition among these crops. We estimate fixed and random effects models for double log demand equations and a complete demand system, the Almost Ideal Demand System. The latter specification can be used to estimate demand relationships that conform to utility maximising behaviour. The elasticity estimates are very robust across the different specifications and estimation methods. This increases confidence in our findings and provides some assurance that choice of functional form or estimation method is not driving our results. We find that retail demands for all berry crops are in the elastic range and that the different berries are substitutes for one another. The demand for strawberries was the least elastic with an own price elasticity of –1.26 and blackberries were the most elastic with a demand elasticity of –1.88. Blackberry demand was also the most responsive to the prices of competing berry crops. The study provides clearer insight into markets for berries in the United States. In addition, it fills a gap in the present lack of up-to-date consumer demand elasticities for these crops and will be useful for growers, decision makers and consumers.